RELAÇÃO ENTRE ESTADO NUTRICIONAL E INFLAMATÓRIO EM PACIENTES RENAIS CRÔNICOS SUBMETIDOS À HEMODIÁLISE. - ALVES, Janete Daniel de Alencar (2017)
Introduction: Chronic kidney disease (CKD) is characterized by progressive and irreversible loss of kidney function. Hemodialysis (HD) is the most commonly renal replacement therapy used among patients with CKD. Despite of the progress achieved in this therapy, nutritional imbalances are frequent associated with malnutrition and overweight, which may be linked to the inflammatory process. Objectives: To evaluate the relationship between nutritional status and inflammation in HD patients. Methods: In this cross-sectional study, 213 hemodialysis patients were analyzed, and ultra-sensitive C-reactive protein (us-CRP) inflammatory biomarker, body mass index (BMI), waist circumference, sagittal abdominal diameter (SAD) nutritional status, and Dual-energy X-ray absorptiometry (DXA) data were investigated. Sociodemographic data was also collected. Spearman correlation, Student's t test and Mann-Whitney test were performed. A multivariate logistic model was adjusted and for all analyzes p <0.05 was adopted as significant. Results: 213 hemodialysis patients (51.4±15.6 y, 59.2% men) was analyzed. Mean values for the BMI were 23.8±4.1kg/m². The prevalence of malnutrition patients was 15.5% and overweight patients was 29.1%. The mean values for us-CRP were 1.04 ± 2.3mg/dL and, regardless of sex, 33.8% of the patients had us-CRP>0.5 mg/dL. In male patients, us-CRP had a positive correlation with percentage body fat (r=0.240, p=0.014), percentage body gynoid (r=0.292, p=0.002) and percentage body android (r=0.216, p=0.027), and a negative correlation with lean body mass (LBM, r=-0.213, p=0.029). In female patients, us-CRP had not only correlated with percentage body gynoid (r=0.133, p=0.238). Patients with higher SAD were three times more chance to have us-CRP> 0.5 mg /dL than patients with lower SAD. Conclusion: In this study, positive correlation between adiposity measurements and high levels of us- CRP was observed, regardless of sex. Negative correlation was only founded between us-CRP and LBM in male patients. Multivariate analysis suggest that the higher LBM was protective factor and increased SAD values were a risk factor for inflammation.